CML – Simulation based software: an effective educational tool for distance learning - Mersni, A.; Buyukdagli, O.; Copra, S.; Khatib, C. (My University, 2022)
Information Technology (IT) education is disrupted by distance learning since it is primarily reliant on hands-on labs and practical experience. In the era of rapid technological change and innovation, the quality of the IT courses offered in higher education is crucial to developing the next generation of IT specialists. In this context, simulation-based software solutions must be adopted immediately to enhance the IT education learning process significantly.
Keywords: Applied Computing; CML; Networks; Virtual tool; NetDevOps; IT Education; Distance learning